Integrated Marketplace Optimization to Enhance the Economic Potential of Agricultural Products in Farmers' Groups in Cikurubuk Village, Sumedang Regency - Fansuri Munawar; Keni Kaniawati; Rini Handayani; Andhi Sukma; Aditya Yudanegara; Sri Wiludjeng SP (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
This Community Service Program aimed to address the challenges faced by farmers in Cikurubuk Village, Sumedang Regency, in marketing their organic rice products. The farmers' limited knowledge of digital marketing and their reliance on traditional methods restricted their market reach and competitiveness. The program aims to enhance farmers’ digital skills by teaching them how to effectively use e-commerce platforms and optimize their branding strategies. The method included three stages: a survey to identify the needs and challenges of the community, training sessions on digital marketing, visual content creation, and branding, followed by mentoring to support participants in implementing these skills. The survey highlighted a significant gap in digital literacy, while the training provided practical knowledge on managing online stores, creating visually appealing product content, and developing strong product branding. Ongoing mentoring helped participants apply these skills effectively in their businesses. The results show that participants demonstrated significant improvements in utilizing digital platforms, enhancing their brand visibility, and attracting more consumers, both locally and nationally. The program led to a notable increase in product visibility and sales, boosting the economic potential of the farmers' businesses. In conclusion, this program successfully empowered local farmers by expanding their knowledge of digital technology and e-commerce, thereby improving their market reach and product competitiveness. This initiative has positively impacted the economic development of Cikurubuk Village and could serve as a model for similar community empowerment programs. It is hoped that this program will inspire other villages to develop by optimizing digital technology to market their regional products